Antimicrobial Effect and the Mechanism of Diallyl Trisulfide against Campylobacter jejuni - Yuanyue Tang; Fengming Li; Dan Gu; Wenyan Wang; Jinlin Huang; Xinan Jiao (MDPI AG, 2021)
Campylobacter jejuni is an important foodborne pathogen causing campylobacteriosis. It can infect humans through the consumption of contaminated chicken products or via the direct handling of animals. Diallyl trisulfide (DATS) is a trisulfide compound from garlic extracts that has a potential antimicrobial effect on foodborne pathogens. This study investigated the antimicrobial activity of DATS on C. jejuni by evaluating the minimal inhibitory concentrations (MICs) of C. jejuni 81-168, and fourteen C. jejuni isolates from chicken carcasses. Thirteen of 14 C. jejuni isolates and 81-176 had MICs ≤ 32 μg/mL, while one isolate had MIC of 64 μg/mL. Scanning electron microscopy (SEM) analysis showed the disruption and shrink of C. jejuni bacterial cell membrane after the DATS treatment. A time-killing analysis further showed that DATS had a dose-dependent in vitro antimicrobial effect on C. jejuni during the 24 h treatment period. In addition, DATS also showed an antimicrobial effect in chicken through the decrease of C. jejuni colony count by 1.5 log CFU/g (cloacal sample) during the seven-day DATS treatment period. The transcriptional analysis of C. jejuni with 16 μg/mL (0.5× MIC) showed 210 differentially expression genes (DEGs), which were mainly related to the metabolism, bacterial membrane transporter system and the secretion system. Fourteen ABC transporter-related genes responsible for bacterial cell homeostasis and oxidative stress were downregulated, indicating that DATS could decrease the bacterial ability to against environmental stress. We further constructed five ABC transporter deletion mutants according to the RNA-seq analysis, and all five mutants proved less tolerant to the DATS treatment compared to the wild type by MIC test. This study elucidated the antimicrobial activity of DATS on C. jejuni and suggested that DATS could be used as a potential antimicrobial compound in the feed and food industry.